Overview and recording of sensors and corresponding biosignal measurement technologies (Biosensors) - Communication protocols - Ethical issues - Κοτοπούλη (Maria-Ioanna Kotopouli) Μαρία - Ιωάννα (Bioethica, 2018)
Chronic diseases represent the major expense in healthcare today. Examples include diabetes, asthma, heart failure, chronic obstructive pulmonary disease (COPD), dementia, arthritis, and a number of neurological disorders. The World Health Organization estimates that chronic diseases are the main cause of "disability" in 2020 and that, if not managed properly, will become the most expensive problem for healthcare systems .One of the main goals of modern health care is to ensure that patients with chronic and non-diseases (such as diabetes and COPD), will receive medical monitoring and care at home whenever possible. This would result in lower requirements in necessary sources of health care, in hospital coverage and allow for more targeted delivery of health and care services. Therefore the problem we face is the reliable, easy and fast collection of medical data, i.e. the state of health of an individual. The development of sensor technology, in hardware and software, but also the communication protocols, has enabled wearable, ambient, implantable sensors to be introduced into health service systems. Ideally, this would permit the monitoring of physiological parameters of the patient continuously in contrast to provide a "snapshot" of these parameters when the patient visits the physician or performing some tests. This paper seeks to investigate and analyze simple glucose, pressure, oxygen, and more complex sensor systems available on the market or at research level and to review the communication protocols used in these applications, with particular emphasis on emerging bioethics.